Prevalence and spectrum of AKT1, PIK3CA, PTEN and TP53 somatic mutations in Chinese breast cancer patients. - Guoli Li; Xinwu Guo; Ming Chen; Lili Tang; Hui Jiang; Julia X Day; Yueliang Xie; Limin Peng; Xunxun Xu; Jinliang Li; Shouman Wang; Zhi Xiao; et al. (PLoS ONE, 2018)
Breast cancer, one of the most frequently occurring cancers worldwide, is the leading cause of cancer-related death among women. AKT1, PIK3CA, PTEN and TP53 mutations were common observed in breast cancer representing potential clinical biomarkers for cancer classification and treatment. A comprehensive knowledge of AKT1, PIK3CA, PTEN and TP53 mutations in breast cancer was still insufficient in Chinese population. In this study, the complete coding regions and exon-intron boundaries of AKT1, PIK3CA, PTEN and TP53 genes were sequenced in paired breast tumor and normal tissues from 313 Chinese breast cancer patients using microfluidic PCR-based target enrichment and next-generation sequencing technology. Total 120 somatic mutations were identified in 190 of the 313 patients (60.7%), with the mutation frequency of AKT1 as 3.2%, PIK3CA as 36.4%, PTEN as 4.8%, and TP53 as 33.9%. Among these mutations, 1 in PIK3CA (p.I69N), 3 in PTEN (p.K62X, c.635-12_636delTTAACCATGCAGAT and p.N340IfsTer4) and 5 in TP53 (p.Q136AfsTer5, p.K139_P142del, p.Y234dup, p.V274LfsTer31 and p.N310TfsTer35) were novel. Notably, PIK3CA somatic mutations were significantly associated with ER-positive or PR-positive tumors. TP53 somatic mutations were significantly associated with ER-negative, PR-negative, HER2-positive, BRCA1 mutation, Ki67 high expression and basal-like tumors. Our findings provided a comprehensive mutation profiling of AKT1, PIK3CA, PTEN and TP53 genes in Chinese breast cancer patients, which have potential implications in clinical management.